EFEKTIFITAS BUERGER ALLEN EXERCISE DENGAN RANGE OF MOTION (ROM) TERHADAP NILAI SENSITIFITAS KAKI PADA PASIEN DIABETES MELITUS TIPE II - Irhas Syah; Rahmiwati Rahmiwati; Rola Oktorina (LLDIKTI Wilayah X, 2021)
One of the complications of diabetes mellitus is the complication caused by circulatory disorders in the lower extremities, causing diabetic injuries to the feet of patients with diabetes mellitus which lead to amputation. In order to reduce the number of incidents, it is necessary to carry out activities to increase circulation in the lower extremities of diabetes mellitus patients, including ROM and Buerger Allen exercise. This study aims to determine the differences in the effectiveness of ROM and buerger allen exercise with the sensitivity of the feet of patients with Type II Diabetes mellitus. The study used a Quasi Experiment design with two groups posttest only design with 80 respondents divided into 2 groups, namely which were: the groupthat gave with ROM exercises and the group with the Buerger Allen Exercise. The measuring instrument used was the 10-g Monofilament Test. The results of this researchers found that the two interventions had a significant effect on the sensitivity of the feet of patients with diabetes mellitus with a P value <0.05, however, there were a differences ini the change in the mean before and after the Buerger Allen Exercise for 0.82, while the sensitivity of the feet in ROM intervention was 0.55. ROM exercises and Buerger Allen Exercise can be applied by people with diabetes mellitus in treating DM foot